Cadmium benzylphosphonates – the close relationship between structure and properties. Issue 39 (24th September 2019) - Akhmetova, Irina; Beyer, Sebastian; Schutjajew, Konstantin; Tichter, Tim; Wilke, Manuel; Prinz, Carsten; Martins, Inês C. B.; Al-Sabbagh, Dominik; Roth, Christina; Emmerling, Franziska
Abstract : Structure-properties relationship of new Cd-benzylphosphonates differing in their fluorine content. Abstract : Cadmium benzylphosphonate Cd(O3 PBn)·H2 O (1 ) and its fluorinated derivates Cd(O3 PBn-3F)·H2 O (2 ), Cd(O3 PBn-4F)·H2 O (3 ), and Cd(O3 PBn-F5)·H2 O (4 ) were synthesized mechanochemically. The crystal structures of the compounds were determined based on powder X-ray diffraction (PXRD) data. The influence of the ligand substitution on the crystal structure of the metal phosphonate was determined. The hydrophobicity as a function of degree of fluorination was investigated using dynamic vapor sorption.